Optimizing a camu camu nectar (Myrciaria dubia) using response surface methodology - Bernabé Luza, Freddy (2015)
To optimize a formulation of camu camu (Myrciaria dubia) nectar, a Response surface methodology (RSM) was used. The variables were: sacarose and water and the response was the general acceptability. The methodology employed three stages: Screening and Path of Steepest Ascent with a 2k Factorial design and centrals points with 9 treatments each one and a final optimization with a Central Composite Rotatable design with 13 treatments. The optimal levels of the variables were obtained: sacarose (79,95 g) and water (301,22 g). Sensory analysis and stability test with a time of shelf life of 80 days were performed.